Milk of calcium: A rare manifestation of juvenile dermatomyositis - Deniz Gezgin YILDIRIM,; İsmail AKDULUM,; Beril TALİM,; Ercan DEMİR,; Necla BUYAN,; Sevcan A. BAKKALOĞLU, (Archives of Rheumatology, 2021)
Juvenile dermatomyositis (JDM) is a chronic autoimmune disease characterized by systemic capillary vasculopathy, which leads to proximal myopathy and pathognomonic skin rashes.[1,2] Herein, we report a patient who was diagnosed with JDM complicated with an extremely rare event, known as ‘milk of calcium’ formation. A 3.5-year-old girl was referred to our clinic with complaints of muscle weakness, rash on her cheeks, periorbital area and extensor surface of her hands for two years. Physical examination revealed heliotrope rash, Gottron’s papules and calcinosis on the right lateral thigh. Mildly elevated acute phase reactants and muscle enzyme levels were detected. Anti-nuclear antibody and rheumatoid factor were negative, while anti-melanoma differentiation- associated gene 5 antibody was positive. The lower extremity magnetic resonance imaging (MRI) showed myositis and electromyography showed diffuse proximal myopathy. In deltoid muscle biopsy, the major histocompatibility class-I expression was shown to be increased, which is compatible with early histological finding of JDM. MRI and ultrasonography (USG) showed a large collection area containing calcified liquid material, ‘milk of calcium’, in the right lower limb muscle groups (Figure 1). The diagnosis of JDM was confirmed according to Bohan and Peter criteria.[3] The collection was drained under USG guidance, and high calcium and phosphorus values were detected in the aspiration material. 2 mg/kg/day oral prednisolone, nine doses of monthly 2 gr/kg intravenous immunoglobulin (IVIG), and subcutaneously 15 mg/m2/week methotrexate (MTX) were prescribed. Corticosteroid therapy was gradually tapered after the first month of therapy and continued as a low dose. The muscle weakness disappeared, but the milk of calcium did not regress. Four doses of intravenous pamidronate (1 mg/kg) three months apart and six doses of monthly 500 mg/m2 cyclophosphamide were added to the therapy. At the one-year follow-up, a prominent regression in milk of calcium collection was observed. A written informed consent was obtained from the patient’s parents. <f1> Calcinosis is one of the most substantial sequelae of JDM, seen in 30-70% of patients. It is associated with delay in diagnosis and treatment, inadequate therapy, organ involvement, joint contractures and lipodystrophy.[2,4] Tissue injury resulting from trauma or inflammation triggers the deposition of insoluble calcium salts in subcutaneous tissues, muscles and skin.[5,6] Soft tissue swelling in JDM patients should raise a suspicion about the development of milk of calcium.[7] This lesion can be determined by MRI and USG, and differentiated from infection and hemorrhage.[8,9] Mukamel et al.[10] reported two children with JDM who had presented with milk of calcium. Drainage material showed increased levels of pro-inflammatory cytokines and alendronate showed a beneficial effect on the treatment of this condition. Calcinosis treatment remains controversial, and multiple treatment strategies, such as calcium channel blockers, bisphosphonates, probenecid, aluminum hydroxide, thalidomide, colchicine, intralesional steroids, rituximab, infliximab and IVIG have been attempted with variable success rates.[4,5,11,12] In our case, the calcinosis was resistant to steroids, MTX and IVIG treatments, but cyclophosphamide and pamidronate therapies showed a beneficial effect leading to the regression of milk of calcium. Juvenile dermatomyositis may be confronted with various clinical findings apart from the typical cutaneous changes. A longer diagnosis lag time and treatment delay in JDM could lead to severe complications which are resistant to conventional therapies. Milk of calcium is an extremely rare but one of the most devastating complications of JDM which may gain benefit from cyclophosphamide and pamidronate therapies.